Emerging Liver–Kidney Interactions in Nonalcoholic Fatty Liver Disease. Issue 10 (October 2015) - Musso, Giovanni; Cassader, Maurizio; Cohney, Solomon; Pinach, Silvia; Saba, Francesca; Gambino, Roberto
Abstract : Mounting evidence connects non-alcoholic fatty liver disease (NAFLD) to chronic kidney disease (CKD). We review emerging mechanistic links between NAFLD and CKD, including altered activation of angiotensin converting enzyme (ACE)-2, nutrient/energy sensors sirtuin-1 and AMP-activated kinase, as well as impaired antioxidant defense mediated by nuclear factor erythroid 2-related factor-2 (Nrf2). Dietary fructose excess may also contribute to NAFLD and CKD. NAFLD affects renal injury through lipoprotein dysmetabolism and altered secretion of the hepatokines fibroblast growth factor-21, fetuin-A, insulin-like growth factor-1, and syndecan-1. CKD may mutually aggravate NAFLD and associated metabolic disturbances through altered intestinal barrier function and microbiota composition, the accumulation of uremic toxic metabolites, and alterations in pre-receptor glucocorticoid metabolism. We conclude by discussing the implications of these findings for the treatment of NAFLD and CKD. Trends: A growing body of data suggests liver–kidney crosstalk in NAFLD, and recent findings have provided insight into the mechanisms underlying this crosstalk. These mechanistic insights have highlighted potential therapeutic targets for the treatment NAFLD. The mechanisms associated with liver–kidney crosstalk in NAFLD include altered RAS and AMPK activation, impaired antioxidant defense, and excessive dietary fructose intake. NAFLD affects renal injury through altered lipoprotein and hepatokine secretion. CKD aggravates NAFLD by modulating intestinal microbiota, uremic toxin accumulation, and by altered pre-receptor glucocorticoid metabolism.